Fire in the mind - Julia, Raul.; Vecchione, Judith; DeBeaufort, Marc.; Campos, Yezid; WGBH (Television station : Boston, Mass.); Channel Four (Great Britain); Central Independent Television (South Burlington, VT : Annenberg/CPB Collection, 1993)
As Latin American countries struggle to come to terms with their problems, many demand fundamental structural change - revolution. This program focuses on revolutions in two countries: El Salvador and Peru. It examines the conflict in El Salvador, rooted in issues of land and poverty and where some of the problems are being addressed. But in Peru, serious economic conditions and poverty have resulted in a violent and more deadly revolutionary group, the Shining Path.
Title on container: Fire in the mind: revolutions and revolutionaries.
In English and Spanish, with English subtitles and voiceovers.
VHS format.
Raul Julia, narrator.
Keywords: Sendero Luminoso (Guerrila group); Insurgency -- El Salvador; Insurgency -- Peru; El Salvador -- Politics and government -- 1979-; El Salvador -- Social conditions; El Salvador -- Economic conditions; Peru -- Politics and government -- 1980-; Peru -- Social conditions